Differences in Spatial Mathematical Ability of Students Given A Model Learning Realistic Mathematis Education With STAD Type Of Cooperative Learning - Ara Yustiana; Edi Syahputra; Anita Yus (Mathematics Education Study Program, 2020)
The focus of this research is to analyze the students' spatial abilities and mathematical dispositions in 2 cooperative learning models. This study aims to determine (1) Is there any significant difference between students' spatial abilities taught by using Realistic Mathematic Education (RME) learning and students' spatial abilities taught by using STAD type of cooperative learning? (2) is there any interaction between learning and students' initial mathematics abilities against students' spatial abilities ? This research is a quasi-experimental research. The population of this study were students of class X MAN 2, 2019/2020 Deli Serdang. The research sample was taken randomly in order to obtain two sample classes. The experimental class I received the Realistic Mathematic Education (RME) learning model and the experimental class II received the STAD type of cooperative learning. The instrument are consisted of a spatial ability test and a learning disposition questionnaire. Data analysis was performed using two-way analysis of variance (ANOVA). The results showed that (1) there was a significant difference between students' spatial abilities taught by using Realistic Mathematic Education (RME) learning and students' spatial abilities taught by using STAD type of cooperative learning (2) there was an interaction between learning and students' initial mathematical abilities towards their spatial abilities.